European Achondroplasia Forum guiding principles for the detection and management of foramen magnum stenosis - Irving, Melita; AlSayed, Moeenaldeen; Arundel, Paul; Baujat, Geneviève; Ben-Omran, Tawfeg; Boero, Silvio; Cormier-Daire, Valérie; Fredwall, Svein; Guillen-Navarro, Encarna; Hoyer-Kuhn, Heike-Katharina; Kunkel, Philip Oskar Sean; Lampe, Christian Gerhard; et al. (Orphanet journal of rare diseases, 2023)
Foramen magnum stenosis is a serious, and potentially life-threatening complication of achondroplasia. The foramen magnum is smaller in infants with achondroplasia, compared with the general population, and both restricted growth in the first 2 years and premature closure of skull plate synchondroses can contribute to narrowing. Narrowing of the foramen magnum can lead to compression of the brainstem and spinal cord, and result in sleep apnoea and sudden death. There is a lack of clarity in the literature on the timing of regular monitoring for foramen magnum stenosis, which assessments should be carried out and when regular screening should be ceased. The European Achondroplasia Forum (EAF) is a group of clinicians and patient advocates, representative of the achondroplasia community. Members of the EAF Steering Committee were invited to submit suggestions for guiding principles for the detection and management of foramen magnum stenosis, which were collated and discussed at an open workshop. Each principle was scrutinised for content and wording, and anonymous voting held to pass the principle and vote on the level of agreement. A total of six guiding principles were developed which incorporate routine clinical monitoring of infants and young children, timing of routine MRI screening, referral of suspected foramen magnum stenosis to a neurosurgeon, the combination of assessments to inform the decision to decompress the foramen magnum, joint decision making to proceed with decompression, and management of older children in whom previously undetected foramen magnum stenosis is identified. All principles achieved the ≥ 75% majority needed to pass (range 89-100%), with high levels of agreement (range 7.6-8.9). By developing guiding principles for the detection and management of foramen magnum stenosis, the EAF aim to enable infants and young children to receive optimal monitoring for this potentially life-threatening complication.
Veröffentlicht: 27. Juli 2023
Gesehen am 11.10.2023